Preparation and characterization of conducting polyaniline and polyaniline-titanium(iv) oxide composite blended with poly(vinyl alcohol) - Chan, Yen Nee (2005)
Conductive polyaniline (PAni) and polyaniline-titanium(IV) oxide (PAni- TiO2) composites were prepared by chemical oxidative polymerization of aniline in the presence of dodecylbenzene sulfonic acid (DBSA) in HCl medium, which played both the role as dopant and surfactant. Such processable conductive PAni and its composite were blended with poly(vinyl alcohol) (PVA) in water, which was then cast into film by solution casting, resulting a flexible, free-standing and conductive blend films. The morphology of the PAni/PVA and PAni-TiO2/PVA blends was confirmed by using scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Generally, the thermogravimetric analysis (TGA) curves of the blends showed gradual weight loss due to absorbed moisture and solvent upon initial heating up to around 100 oC, followed by a slow weight loss until around 225 oC, which could be attributed to the elimination of dopant. The final degradation of the polymer occurs from around 227 to 900 oC. The presence of a single Tg as revealed by differential scanning calorimetry (DSC) and its shifts to higher value with increasing PAni and PAni-TiO2 content, revealing the miscibility between PAni and PAni-TiO2 with PVA through hydrogen bonding as shown by FTIR. The X-ray diffraction pattern of the blends revealed that the degree of crystallinity of PAni-TiO2/PVA blends was lower than that of PVA and TiO2, showing that the amorphous nature of PAni may inhibit crystallization of TiO2 and PVA. The electrical conductivity of the PAni-TiO2/PVA blends increase with the increase of TiO2/aniline weight ratio and reaches a saturation value at weight ratio of 0.13. All the blends samples exhibit similar pattern, i. e. the conductivity increases with temperature from 30 oC to 50 oC, following with decreasing conductivity, and reach the maximum at 140 oC, then decrease with further increasing temperature. PAni/PVA and PAni-TiO2 (I)/PVA show maximum conductivity at 40 oC, 1.69 and 1.78 S/cm, respectively. The blends films exhibited good conductivity even at low weight fraction of conductive components, with conductivity value around 10-5 S/cm. The electrical conductivity of the films increases with increasing content of conducting PAni and PAni-TiO2 content in the PVA matrix; indicating the dependence of the blended film conductivity upon the PAni and PAni-TiO2 content. This was due to the growing of continuous network formation, which is confirmed by TEM. The percolation threshold was about 2.0 wt. % for both PAni/PVA and PAni-TiO2/PVA blends. From the Hall effect studies, the conductivity and carrier mobility are linearly related while the carrier mobility are inversed of the carrier density. At room temperature, PAni-TiO2 (I)/PVA blend (40 wt. %) shows the highest carrier mobility (4878 cm2 volt-1 sec-1) among the samples. Finally, the conductivity of the blends decreases as the temperature is increased and deviates strongly from variable range hopping equation above 300 K.